COMPARATIVE STUDY BETWEEN CONVENTIONAL INFERIOR TURBINECTOMY AND ENDOSCOPIC INFERIOR TURBINOPLASTY FOR TREATMENT OF INFERIOR TURBINATE HYPERTROPHY - Rafique, Atif; Raza, Maqbool; Khattak, Shahid Farooq; Ali, Muhammad; Azam, Khalid; Zubair, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare efficacy of endoscopic turbinoplasty versus conventional inferior turbinectomy for hypertrophy of inferior turbinate.Study Design: Comparative prospective study.Place and Duration of Study: Ear, Nose and Throat (ENT) Department Combined Military Hospital (CMH) Multan, from Jun 2019 to May 2020.Methodology: This study comprised of 50 patients of various age groups and both genders. Patients were grouped into two groups A and B, each group having 25 patients through random sampling. Patients in group A had endoscopic turbinoplasty whereas patients in group B had partial turbinectomy through conventional surgical method. Patients were followed regularly in both groups and were inspected postoperatively at 2 weeks, after 1 month and after 3 months.Results: Patients who underwent Endoscopic turbinoplasty experienced less pain (p˂0.05) postoperatively at 2 weeks compared to conventional surgical turbinectomy. In addition, these patients showed statistically significant healing and reduced crusting at 1 month postoperatively. At 3 months post operatively all patients had healed completely as opposed to only 72% with surgical turbinectomy.Conclusion: Endoscopic turbinoplasty is more effective than conventional surgical technique for inferior turbinate hypertrophy as it leads to less post-operative pain, reduced nasal crusting and earlier healing.